2020
DOI: 10.3390/catal10030295
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanisms of Guaiacol Pyrolysis Based on Free Radicals Detection Technology

Abstract: In order to understand the reaction mechanism of lignin pyrolysis, the pyrolysis process of guaiacol (o-methoxyphenol) as a lignin model compound was studied by free radical detection technology (electron paramagnetic resonance, EPR) in this paper. It was proven that the pyrolysis reaction of guaiacol is a free radical reaction, and the free radicals which can be detected mainly by EPR are methyl radicals. This paper proposes a process in which four free radicals (radicals 1- C6H4(OH)O*, radicals 5- C6H4(OCH3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Without the presence of a catalyst, a GUA conversion rate of only 20% was obtained, yielding 60% of ( 5) with no formation of the HDO products ( 1)-( 3). At the current stage, we speculate that (5) was formed via a free radical mechanism rather than transalkylation in the absence of a catalyst, similar to that reported in the pyrolysis of guaiacol [62].…”
Section: Catalytic Hdo Of Guasupporting
confidence: 78%
“…Without the presence of a catalyst, a GUA conversion rate of only 20% was obtained, yielding 60% of ( 5) with no formation of the HDO products ( 1)-( 3). At the current stage, we speculate that (5) was formed via a free radical mechanism rather than transalkylation in the absence of a catalyst, similar to that reported in the pyrolysis of guaiacol [62].…”
Section: Catalytic Hdo Of Guasupporting
confidence: 78%
“…Studies on representative lignin building blocks, such as guaiacol, syringol and eugenol, can provide detailed insight into the (catalytic) pyrolysis mechanism. 8–12 Li et al used electron paramagnetic resonance (EPR) spectroscopy to show that guaiacol pyrolysis is a radical-driven process and catechol is a favored product due to the presence of mobile hydrogen atoms. 8 Verma and Kishore carried out density functional theory (DFT) calculations and showed that the lowest-energy unimolecular decomposition pathway of eugenol yields guaiacol.…”
Section: Introductionmentioning
confidence: 99%
“… 8–12 Li et al used electron paramagnetic resonance (EPR) spectroscopy to show that guaiacol pyrolysis is a radical-driven process and catechol is a favored product due to the presence of mobile hydrogen atoms. 8 Verma and Kishore carried out density functional theory (DFT) calculations and showed that the lowest-energy unimolecular decomposition pathway of eugenol yields guaiacol. 9 Detailed mechanistic studies exist for benzaldehyde, 13 phenol, 14 dimethoxybenzenes 15 and larger model systems, such as 4-phenoxyphenol and 2-methoxy-phenoxybenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Since the structure of this natural polymer is extremely complex, model compounds are often used to study its conversion to high value-added chemicals [8,10]. Ferulic and vanillic acids, as well as pyrocatechol and guaiacol are common products of lignin processing [1,8,[11][12][13], and therefore are often used as model lignin compounds [4,8,11,[14][15][16][17]. These compounds are lignin structural units of various sizes and contain almost the entire list of functional groups present in the lignin macromolecule.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is commonly used for lignin processing due to its ability to effectively separate this polymer's strong structure [8,11,33,34]. However, high-temperature conversion of these raw materials generates a large number of final pyrolysis products.…”
Section: Introductionmentioning
confidence: 99%